"From souvenirs to 3D printed souvenirs". Exploring the capabilities of additive manufacturing technologies in (re)-framing tourist souvenirs. (April 2019) - Anastasiadou, Constantia; Vettese, Sam
Abstract: Souvenirs, whether mass-produced commodities made elsewhere or local artisanal handicrafts, are static objects that lack the capacity to mediate or generate the co-creative, active or immersive experiences that tourists desire. The expansion of additive manufacturing (3D printing) and open access digital fabrication facilities creates opportunities for personalisation, creativity and prosumption that could alter souvenir consumption. Using a qualitative approach, this study examined visitor preferences and managers views on 3D printed souvenirs that were mass-produced but individualised within a heritage retail environment, where the visitors were able to interact with the digital making process. The findings suggest that while there is some interest in designing and personalising souvenirs using new technologies, there are also intellectual and ethical challenges which need to be addressed. We propose the 3D printed souvenir as a new type of souvenir and a future research agenda that considers the technology implications for tourist consumption. Highlights: Souvenirs are passively consumed and lack co-creative and experiential features. 3D printing can transform souvenirs from passive to experiential objects. Some visitors desire further involvement in souvenir design and personalisation. Managers identified challenges in adopting 3D printing for souvenir production. A research agenda and future implications of 3D printing in tourism are considered.